Microstructural Study of the Interfacial Transition Zone in Concrete using Optical Microscopy - Ismail Khairul Nizar; Let Hui Tan (MATEC Web of Conferences, 2017)
This paper presents an overview on the optical microstructural features in concrete. Microstructure is the small scale structure of a material, defined as the structure of a prepared surface of material as revealed by a microscope. The concrete specimens with the manipulation of water/cement ratio 0.3-0.7 (increment of 0.1) in the concrete mix design were used to study the optical microstructural features in concrete and to validate the existence of an interfacial transition zone (ITZ) in concrete. USB Digital Microscope is used to analyse the formation mechanism of microstructure in concrete where the optical microstructural images is analyse via respective curing periods of 1, 7, 28 and 56 days. The microstructure features are discussed with respect to their influence on the strength development of concrete.